Truncated nonsmooth newton multigrid methods for convex minimization problems - Gräser, Carsten; Sack, Uli; Sander, Oliver (Lecture Notes in Computational Science and Engineering, 2009)
We present a new inexact nonsmooth Newton method for the solution of convex minimization problems with piecewise smooth, pointwise nonlinearities. The algorithm consists of a nonlinear smoothing step on the fine level and a linear coarse correction. Suitable postprocessing guarantees global convergence even in the case of a single multigrid step for each linear subproblem. Numerical examples show that the overall efficiency is comparable to multigrid for similar linear problems. © 2009 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2022-03-23